Analisis Hasil Uji Tarik dan SEM pada Obyek Cetak 3D dari Filamen Limbah Plastik PET - Tri Hannanto Saputra; Ariawan, Radhi; Nur Akhlis Sarihidaya Laksana; Unggul Satria Jati; Dikky Kusuma Wijaya (P3M Politeknik Negeri Cilacap, 2025)
3DPrinting filament from PET plastic bottle waste is one appropriate solution to overcome PET plastic waste. This research aims to develop a PET plastic bottle waste recycling method using extrusion technology into 3DPrinting filament. The filament formed is used in the printing process using a 3DPrinting FDM machine. The printed object specimens were Dogbone ASTMD638 Type V. Previous research used tensile test and macroscopy photography methods to observe the tensile strength. This research used filament-making, tensile test, and SEM test methods. This research showed that PET plastic bottle waste can be recycled into 3DPrinting filaments. Based on the tensile test result, the average maximum tensile stress from lowest to highest in the sequence was 7.4 MPa, 12.4 MPa, and 14.9 MPa. The type of fracture that occurred in the specimen with the highest maximum tensile strength was a brittle fracture.